Learning Persistence from an Islamic Perspective; Instrument Development Study and Its Correlation with Learning Outcomes - Mukhoiyaroh, Mukhoiyaroh; Aziz, Yahya (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Persistence is important for students to form a personality with tough character in facing difficulties based on faith in Allah SWT. This study aims to develop an Islamic Perspective Learning Persistence instrument and find its correlation with learning outcomes. This research approach is quantitative research using exploratory factor analysis (EFA). The development of the Islamic Perspective Learning Persistence instrument is then carried out to study the effect of Islamic perspective learning persistence on learning outcomes with multiple linear regression tests. Respondents are students at MAN 3 Jombang class XI, with a sample representing class XI as many as 156 male and female students. The results showed that there were five factors formed from the EFA test of Islamic perspective learning persistence, namely the intention of worship because of Allah, patience with effort, istiqomah or never giving up, husnudzan towards Allah and husnudzan towards one's abilities. The study's results with the Simultaneous test (F) and the analysis of the coefficient of determination show that Islamic perspective learning persistence simultaneously influences student learning outcomes. The dominant factors that support learning outcomes from an Islamic perspective are patience with effort (11.0%) and husnudzan to Allah SWT in helping students’ learning difficulties (8.2%). The other three factors proved to be less dominant in improving students' learning outcomes.